Exploring the Challenges Encountered by Sixth-Semester Students of English Education in Comprehending English Academic Journal Articles - Nurul Tri Wahyuni (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study explores the challenges faced by sixth-semester students of an English Education program in comprehending English academic journal articles. While previous studies have discussed general reading comprehension in EFL contexts, limited attention has been given to students lived experiences in reading authentic academic journals and the strategies they use to cope with these difficulties. To address this gap, this study employed a qualitative approach using in-depth interviews with six students who regularly engage with academic journal articles. The findings reveal that students experience major difficulties related to academic vocabulary, technical terms, and complex sentence structures. The methodology and results sections were identified as the most challenging due to their use of statistical terminology and dense explanations. Topic familiarity also played a significant role in comprehension, with unfamiliar or highly theoretical topics increasing reading difficulty. To overcome these challenges, students relied on rereading, digital tools such as online dictionaries and translation applications, peer discussions, and summarizing key points. These findings indicate that students’ difficulties in reading academic journals are influenced by both linguistic and disciplinary factors. The study highlights the need for targeted academic reading instruction that focuses on academic vocabulary development, structural awareness, and guided practice with research articles. By presenting students’ perspectives, this research contributes to a deeper understanding of academic reading challenges in EFL higher education contexts.